2015
DOI: 10.1088/1674-1056/24/4/043101
|View full text |Cite
|
Sign up to set email alerts
|

Selection rules for electric multipole transition of diatomic molecule in scattering experiments

Abstract: The knowledge of the energy level structures of atoms and molecules is mainly obtained by spectroscopic experiments. Both photoabsorption and photoemission spectra are subject to the electric dipole selection rules (also known as optical selection rules). However, the selection rules for atoms and molecules in the scattering experiments are not identical to those in the optical experiments. In this paper, based on the theory of the molecular point group, the selection rules are derived and summarized for the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…The assignments of the transitions in this work are based on the previous photoabsorption works. The present measured spectra consist of the transitions of (a 1 σ*, 4s, 4p, 3d) ← 2t 1 , (a 1 σ*, 4s, 4p, 3d) ← 7t 2 , and (a 1 σ*, 4p) ← 2e, and the spectrum measured at 4.5° is shown in Figure a. The present electron energy loss spectra include the dipole-forbidden transitions of a 1 σ* ← 2t 1 , a 1 σ* ← 2e, III, and 3d ← 7t 2 due to the relaxation of the selection rules at nonzero scattering angles in the fast electron collision experiment. , The features at 8.64, 9.97, and 10.26 eV are tentatively labeled as I, II, and III in this work since it is difficult to assign them clearly. Feature I has been observed in the photoabsorption spectrum as a weak shoulder; however, it is much stronger than the adjacent features in the large scattering angles as shown in Figure .…”
Section: Experimental and Calculation Methodsmentioning
confidence: 72%
“…The assignments of the transitions in this work are based on the previous photoabsorption works. The present measured spectra consist of the transitions of (a 1 σ*, 4s, 4p, 3d) ← 2t 1 , (a 1 σ*, 4s, 4p, 3d) ← 7t 2 , and (a 1 σ*, 4p) ← 2e, and the spectrum measured at 4.5° is shown in Figure a. The present electron energy loss spectra include the dipole-forbidden transitions of a 1 σ* ← 2t 1 , a 1 σ* ← 2e, III, and 3d ← 7t 2 due to the relaxation of the selection rules at nonzero scattering angles in the fast electron collision experiment. , The features at 8.64, 9.97, and 10.26 eV are tentatively labeled as I, II, and III in this work since it is difficult to assign them clearly. Feature I has been observed in the photoabsorption spectrum as a weak shoulder; however, it is much stronger than the adjacent features in the large scattering angles as shown in Figure .…”
Section: Experimental and Calculation Methodsmentioning
confidence: 72%
“…For clarification, we use (ν′ = 0) following a state to represent its vibronic ground state. Being different from the photoabsorption spectra where the dipole-allowed transitions dominate, the present electron energy loss spectra include the singlet dipole-forbidden transitions to 3b 2 1 A 2 , 4pb 2 1 A 2 , and 3db 2 1 A 2 states due to the relaxation of the selection rules at nonzero scattering angles in the fast electron collision experiment. , For example, the broad feature in 5.0–7.5 eV shown in Figure consists of both the excitations to the dipole-forbidden 3b 2 1 A 2 state and the dipole-allowed 4sa 1 1 B 1 state. In the range of 7.8–8.1 eV, the previous assignments to the transitions are somewhat controversial.…”
Section: Methodsmentioning
confidence: 73%
“…Being different from the photoabsorption spectra where the dipole-allowed transitions dominate, the present electron energy loss spectra include the singlet dipole-forbidden transitions to 3b 2 1 A 2 , 4pb 2 1 A 2 , and 3db 2 1 A 2 states due to the relaxation of the selection rules at nonzero scattering angles in the fast electron collision experiment. 43,44 For example, the broad feature in 5.0−7.5 eV shown in Figure 1 18,19 However, due to the lack of the transition at 7.85 eV in their works, they assigned the transition at 7.90 eV as the one previously observed at 7.85 eV. By analyzing the present spectra at different scattering angles, it is found that all of the four excitations at 7.85, 7.90, 7.98, and 8.04 eV exist in our spectra.…”
Section: ■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following measurement of the C 1s near-edge photoabsorption spectroscopy of C 2 H 4 indicated the importance of vibronic coupling which provides a mechanism for localized core-hole [22]. However, electron impact method can detect not only the dipole-allowed but also the dipole-forbidden transitions, which can be used to probe the (1sσ g ) −1 (1π g ) 1 state if the core-hole is delocalized [25]. Note that measuring only the excitation processes leads to an incoherent sum of the gerade and ungerade core-hole states, i.e., the inner-shell excitations should include the dipole-allowed (1sσ u ) −1 (1π g ) 1 and dipole-forbidden (1sσ g ) −1 (1π g ) 1 components.…”
Section: Introductionmentioning
confidence: 99%